2007
DOI: 10.1093/humrep/dem081
|View full text |Cite
|
Sign up to set email alerts
|

The number of small antral follicles (2-6 mm) determines the outcome of endocrine ovarian reserve tests in a subfertile population

Abstract: The number of small antral follicles (2-6 mm) is significantly related to age and also, independent of age, to all endocrine ORTs tested, suggesting the number of small antral follicles represents the functional ovarian reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 47 publications
5
69
0
13
Order By: Relevance
“…There is no consensus on identification of the antral follicles (2), however several evidence based studies suggested to select the follicles as antral follicles based on a diameter measurement as 2 to 10 mm. (3)(4)(5)(6)(7)(8)(9)(10). It has been reported that human antral follicles measuring <6 mm express the greatest amount of AMH, and that levels decline with antral follicles increase in size (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on identification of the antral follicles (2), however several evidence based studies suggested to select the follicles as antral follicles based on a diameter measurement as 2 to 10 mm. (3)(4)(5)(6)(7)(8)(9)(10). It has been reported that human antral follicles measuring <6 mm express the greatest amount of AMH, and that levels decline with antral follicles increase in size (23).…”
Section: Discussionmentioning
confidence: 99%
“…The antral follicle count (AFC) have been widely used as the ovarian reserve test, due to convenience of the ultrasonographic tools usage. Follicle counts can be performed easily with the help of the high quality resolution of the sonographic systems (2)(3)(4)(5)(6)(7)(8)(9)(10). Although there are well-known difficulties to obtain correct AFC such as high inter-observer differences and anatomical variations (3), it has been suggested that the ability of AFC to predict poor response might be significantly better than basal FSH.…”
Section: Introductionmentioning
confidence: 99%
“…The number of antral follicles depends on the size of primordial follicle pool from which they are recruited. There are some evidence in the literature that the number of small antral follicles represents the functional ovarian reserve better [18], therefore, small AFC is superior to total AFC in predicting ovarian response. Small AFC is operator-dependent and has intercycle, inter-observer, and intraobserver variability [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…For clinical purpose, some investigators counted the total number of antral follicles with a diameter of 2-10 mm [16], and the others determined the number of antral follicles with a diameter of 2-5 mm [17]. Small antral follicles produce AMH, therefore, they may be better predictors of ovarian reserve and ovarian response than total AFC [18]. Based on these evidence, we preferred to determine the number of small antral follicles with a diameter of 2-6 mm for prediction of high ovarian response in our study.…”
Section: Introductionmentioning
confidence: 99%
“…A Blow^AFC ranges from four to ten follicles and is used as a predictor of both low ovarian reserve and a poor response in IVF cycles. Thresholds for AFC prior to starting IVF and for dosing gonadotropins vary among centers [9,10,2,11]. A potential advantage of AFC is that it can be measured readily in the clinic, generating results immediately.…”
Section: Introductionmentioning
confidence: 99%